The Effect of GDP, Inflation, Exchange Rate, Interest Rate on Stock Price Index In Early Warning System: An Empirical Study In ASEAN-5 Countries - prowanta, embun (Archives of Business Research, 2018)
The objective of the study is to develop an early warning system (EWS) using macroeconomic (gross domestic product, inflation, exchange rate and interest rate) on stock price index in five ASEAN countries (Indonesia, Malaysia, Singapore, Philippines, and Thailand). We used panel data regression and multiple discriminant analyst (MDA) methods to build an early warning system for ASEAN-5 countries. Early warning system of each ASEAN-5 is a model to simulate changes in macroeconomic variables will affect the sensitivity and behavior of ASEAN countries both as a whole and each country against the stock price index. We find that ASEAN 5 countries are sensitive when macroeconomic variables increase and decreasi simultaneously. An autoregressive integrated moving-average (ARIMA) method is used robustness test to early warning system to predict stock price index ASEAN-5 countries. The result of prediction using ARIMA method shows that stock price index Indonesia, Philippines and Thailand are bullish. On the other hand, stock price index Malaysia and Singapore are bearish.